The anterior cingulate cortex contributes to the analgesic rather than the anxiolytic effects of duloxetine in chronic pain-induced anxiety - Li, Chenglin; Ni, Kaiji; Qi, Meiru; Li, Jie; Yang, Kexin; Luo, Yanli (Frontiers in Neuroscience, 2022)
Mood disorders, such as anxiety and depression, are commonly found in people suffering from chronic pain. Serotonin–norepinephrine reuptake inhibitors (SNRIs) are potential in alleviating chronic pain and are the first-line option for anxiety disorder. The anterior cingulate cortex (ACC) plays a vital role in chronic pain-induced anxiety, but its role in the therapeutic effects of SNRIs remains largely unclear. We used complete Freund’s adjuvant (CFA) in this current study to induce chronic inflammatory pain. Von Frey test was used to measure the mechanical withdrawal threshold. The elevated plus maze test (EPM) and the novelty-suppressed feeding test (NSF) were used to measure anxiety-like behaviors. Twenty-one days after the modeling, anxiety-like behaviors were successfully induced in CFA mice, and a 3-day intraperitoneal injection of duloxetine attenuated such behaviors. While, mechanical hyperalgesia was also improved. Then, we locally infused duloxetine in ACC for 3 days only to find out its analgesic effect in CFA mice. Furthermore, we used fiber photometry to discover decreased glutamatergic excitability and enhanced serotonin concentration in ACC after intraperitoneal injection of duloxetine. Overall, this study proposed a potential mechanism for the analgesic effect of duloxetine and shed light on further studies on the mechanism of its anxiolytic effect in chronic pain-induced anxiety.